Graded agaroses directly from seaweed biomass: A sustainable tool for developing clean chemical process. (March 2018) - Vadodariya, Nilesh; Chaudhary, Jai Prakash; Raval, Hiren D.; Meena, Ramavatar
Graphical abstract: Highlights: This paper described "Green" and "Eco-friendly" solution for the preparation of graded agarose from seaweed biomass. Novel grading agent has been demonstrated to produce graded agaroses. This process produced agarose products with desired gelling properties. Gel strength of the products ranging between ca. 100–1600 g cm −2 . Low gelling and melting temperature agarose products from single seaweed biomass. Abstract: Here we describe few novel grading agents (GrA) for the production of graded agaroses directly from seaweed aqueous extract under ambient conditions. Graded agaroses exhibits gelling properties in a wider range (gel strength ≥100–≥1600 gcm −2, gelling temperature ≤27–≥35 °C, and melting temperature ≤72–≥90 °C) which are essential for a variety of molecular biology applications. The uniqueness of this process is the ability to tailor the essential properties of agarose for desired applications, can be achieved from single seaweed aqueous extract by altering initiator nature and/or concentration (w/w) of an initiator in GrA.